Library and information science education and wealth creation: a paradigm shift (2013)
The paper canvasses the idea of a paradigm shift from Library and Information Science (LIS) graduates relying only on paid employment to education with requisite skills capable of producing graduates who will be job and wealth creators. The paper contends that in a knowledge economy, information is a critical resource that must be packaged into products and services which have functional utility value to organizations, individuals and government agencies. It shows that the current LIS curriculum is deficient in marketing strategies and entrepreneurial education orientation necessary for raising professionals who will establish and sustain profitable information product and services firms. There must be conscious effort at creating information needs in an economy through environmental scanning and generating innovative ways of meeting those needs. Consequently, it is recommended that LIS graduates be well equipped with the necessary academic training, skills, and mastery to package and repackage Information and data into consumable knowledge. Also good entrepreneurial skills and marketing strategies training should be integrated into the curriculum at all levels, and. taught by seasoned academics who will inculcate into them the practical capability of same.